2016
DOI: 10.4103/1735-1995.189649
|View full text |Cite
|
Sign up to set email alerts
|

The facilitators and impediment factors of midwifery student′s empowerment in pregnancy and delivery care: A qualitative study

Abstract: Background:The organizational environment and its existing context may deeply affect on empowerment of individuals. In educational institutions as well as other organizations, students are going to be powerful when opportunities for growth and achievement of power are provided for them in learning and educational environments. This study has been carried out to explain the facilitators and impediment factors of midwifery student's empowerment in pregnancy and delivery care.Materials and Methods:The current qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Thus, what is expressed in their answers to the survey is very closely related to their own beliefs, to the training they have received during their degree, and to care practices in general nursing. This distinguishes them from participants in other studies carried out with midwifery students (Janighorban et al, 2016;Nieuwenhuijze et al, 2020).…”
Section: Discussionmentioning
confidence: 93%
“…Thus, what is expressed in their answers to the survey is very closely related to their own beliefs, to the training they have received during their degree, and to care practices in general nursing. This distinguishes them from participants in other studies carried out with midwifery students (Janighorban et al, 2016;Nieuwenhuijze et al, 2020).…”
Section: Discussionmentioning
confidence: 93%
“…In this traditional method, the teacher explains the patient’s condition, the student and teacher examine the patient, and then a decision is taken for diagnosis and treatment. Traditional teacher-centered education methods may lead to inadequately developed clinical skills [ 1 ]. Other studies have shown that midwifery students were not satisfied with clinical skills, supervision, and access to necessary information before clinical education [ 2 , 3 ].…”
mentioning
confidence: 99%